Nanosilver and the microbiological activity of the particulate solids versus the leached soluble silver - Faiz, Merisa B. (2020)
Nanosilver (Ag NPs) is currently one of the most commercialized antimicrobial nanoparticles with as yet, still unresolved cytotoxicity origins. To date, research efforts have mostly described the antimicrobial contribution from the leaching of soluble silver, while the undissolved solid Ag particulates are often considered as being microbiologically inert, serving only as source of the cytotoxic Ag ions. Here, we show the rapid stimulation of lethal cellular oxidative stress in bacteria by the presence of the undissolved Ag particulates. The cytotoxicity characteristics are distinct from those arising from the leached soluble Ag, the latter being locked in organic complexes. The work also highlights the unique oxidative stress-independent bacterial toxicity of silver salt. Taken together, the findings advocate that future enquiries on the antimicrobial potency and also importantly, the environmental and clinical impact of Ag NPs use, should pay attention to the potential bacterial toxicological responses to the undissolved Ag particulates, rather than just to the leaching of soluble silver. The findings also put into question the common use of silver salt as model material for evaluating bacterial toxicity of Ag NPs.